Characteristics of chronic non-specific musculoskeletal pain in children and adolescents attending a rheumatology outpatients clinic : a cross-sectional study - O'Sullivan, Peter; Beales, Darren; Jensen, Lynn; Murray, K.; Myers, T. (Biomed Central, 2011)
Background: Chronic non-specific musculoskeletal pain (CNSMSP) may develop in childhood and adolescence, leading to disability and reduced quality of life that continues into adulthood. The purpose of the study was to build a biopsychosocial profile of children and adolescents with CNSMSP. Methods: CNSMSP subjects (n = 30, 18 females, age 7-18) were compared with age matched pain free controls across a number of biopsychosocial domains. Results: In the psychosocial domain CNSMSP subjects had increased levels of anxiety and depression, and had more somatic pain complaints. In the lifestyle domain CNSMSP subjects had lower physical activity levels, but no difference in television or computer use compared to pain free subjects. Physically, CNSMSP subjects tended to sit with a more slumped spinal posture, had reduced back muscle endurance, increased presence of joint hypermobility and poorer gross motor skills. Conclusion: These findings support the notion that CNSMSP is a multidimensional biopsychosocial disorder. Further research is needed to increase understanding of how the psychosocial, lifestyle and physical factors develop and interact in CNSMSP.